Interactive design of castable shapes using two-piece rigid molds. (May 2019) - Stein, Oded; Jacobson, Alec; Grinspun, Eitan
Highlights: The space of two-piece rigid molds is very restrictive. We introduce a tool to help navigate it and produce castable shapes. The tool is interactive and enables the user to control the design of the shapes. Even though castability is a difficult constraint, we achieve intricate designs. Graphical abstract: Abstract: Two-piece rigid molds are particularly amenable to mass-manufacturing. Arbitrary objects cannot be realized with such a mold, because the cast will collide with the mold during removal. Most shapes are far away from being castable, i.e., realizable with such a two-piece rigid mold. When starting with an arbitrary shape, large deformations are needed to produce castable shapes. Such large deformations require user interaction together with a design process that is aware of fabrication constraints. We present such a design tool to generate two-piece rigid molds separated by a planar cut for a wide variety of shapes. Our casts can be produced in one single piece from a rigid, reusable mold and do not require further assembly after casting. We use a castability energy that can be optimized with gradient-based methods combined with an elastoplastic deformation based on the as-rigid-as-possible method. The tool enables a designer to deform an input shape significantly and arrive at an output shape that is castable.